Why Do We Quote? The Culture and History of Quotation - Finnegan, Ruth (Open Book Publishers, 2011)
Quoting is all around us. But do we really know what it means? How do people actually quote today, and how did our present systems come about? This book brings together a down-to-earth account of contemporary quoting with an examination of the comparative and historical background that lies behind it and the characteristic way that quoting links past and present, the far and the near. Drawing from anthropology, cultural history, folklore, cultural studies, sociolinguistics, literary studies and the ethnography of speaking, Ruth Finnegan's fascinating study sets our present conventions into cross-cultural and historical perspective. She traces the curious history of quotation marks, examines the long tradition of quotation collections with their remarkable recycling across the centuries, and explores the uses of quotation in literary, visual and oral traditions. The book tracks the changing definitions and control of quoting over the millennia and in doing so throws new light on ideas such as 'imitation', 'allusion', 'authorship', 'originality' and 'plagiarism'.